Pengaruh Suku Bunga BI Rate dan BI 7 Day Reverse Repo Rate terhadap Inflasi di Indonesia dengan Metode Vector Autoregression (VAR) - Sari, Yolanda; Herlin, Faradilla; Havilla, Selly (Ekonomis: Journal of Economics and Business, 2024)
This research aims to investigate and analyze the influence of the BI Rate and BI 7 Day Reverse Rate (BI 7 DRRR) on Inflation in Indonesia. The study utilizes secondary data covering BI Rate, BI 7 DRRR and Inflation for the period 2011-2022, obtained from the official website of Bank Indonesia. The research employs a quantitative desciptive approach, employing Vector Autoregression (VAR) as the analytical tool. The findings indicate that the BI Rate has a positive and significant impact on inflation in Indonesia, whereas BI 7 DRRR exhibits a negative and insignificant influence on inflation in Indonesia at a 5% significance level